AS POLÍTICAS EDUCACIONAIS INCLUSIVAS E A FORMAÇÃO DE PROFESSORES PARA A INCLUSÃO NO CURSO DE LICENCIATURA EM LETRAS/ PORTUGUÊS DA UNICENTRO/IRATI - Ingles, Maria Amelia (2015)
This research aimed to investigate the formation of Portuguese Language Course teachers of the State University of the Midwest, Campus de Irati, with respect to the inclusion in education, and as a benchmark for analyzing and discussing the official legislation on inclusion, understood through the development of these policies and the orchestration of the applicability of these theories inclusive in that course design. Based on the theoretical perspective of public policies dealing with inclusive perspectives among others, about inclusive education, as an inalienable human right, which gives citizens the knowledge to live with dignity, he sought a look inside the curricular structure that course in order to expose the search process for inclusive education of future professionals. For we guide us in this goal, we seek to identify the characteristics of the process of implementing the legislation calls for the inclusion in educational training course for teachers of Arts Degree / Portuguese / UNICENTRO / Irati and describe the process by analyzing the menu of disciplines and course design, and to investigate the design of academics and teachers about inclusion. The research was based on SANTOS, 2003b; SANTOS & PAULINE, 2008; GLAT et al, 2006; Mattos, 2006; Spala, 2005; VIANNA, 2005; OGURA, 2002; PIETRO, 2006; MANTOAN, 2006; BRAZIL, 1998; GLAT, Pletsch and Sources, 2007 and the application of techniques and data collection instruments: document analysis, for which I set out to analyze the menus of compulsory and optional subjects of the course. The analysis sought to observe whether and how to include, as defined, is treated during the formation of licensing; semi-structured interviews with teachers and students of the fourth year, duly transcribed, where we analyze the possible implications of these conceptions of inclusion in education training, having as reference the inclusive public policies. We use the Content Analysis (Bardin, 1977) for processing the data, we used techniques and instruments for data analysis. The results showed that, with respect to the inclusion in education, training of academics in Letters / Portuguese presents under construction. Research also shows that teachers and academics recognize the lack of involvement of the subjects who inhabit the institution, but also point to a desire for greater commitment, from both sides. Consider these people who construct and reconstruct every day the history and trajectory of this institution in order to be respected and valued, it seems to be an important step to be taken.